The impact of Chinese investment in resource-rich economies: a case study of Zambia and Nigeria - Mathobela-Nhlapo, Lydia (My University, 2018)
This research examines the impact of Chinese investment in resource-rich economies in Africa. In order to deal with this issue, I have selected Zambia and Nigeria because they provide a platform methodologically for comparison and evaluation on how China is engaging with resource-rich countries. Zambia and Nigeria have become increasingly important to China. Zambia’s copper and Nigeria’s oil reserves are some of the vital resources that are scarce and economically significant toward China’s global economic ambitions. Similarly both these African countries offer China a market for their manufacturing goods, on the other hand, Zambia and Nigeria have benefited from capital inflow, political stature, infrastructure development, an alternative trade partner, human development and security assistance. China’s manufacturing capacity has gained considerable shares in most markets globally, moreover in developing markets by providing low-income consumers with affordable goods, although concerns over their quality is still a major problem. Since becoming a member of the World Trade Organisation (WTO) in 2001, the Asian giant has the greatest number of anti-dumping cases globally, with the largest cases from many African countries. I employ manufacturing as a case study, as it is an effective contributor towards industrial and economic transformation. It boosts technological skills, promotes entrepreneurial activities, and enables entrepreneurs to participate in the global market. However, the influx of Chinese manufactured goods in Zambia and Nigeria has shown to be detrimental towards industrial transformation and competitiveness by crowding out non-Chinese goods, discouraging entrepreneurial activities and strain intra-continental trade. This research has found that Chinese investment has deterred significant economic growth; it further made these economies more resource-reliant, weakened institutions, strengthened political patronage, heightened corruption in resource deals and undermined local manufacturing by crippling local businesses and further strain intra-African trade.
A research report submitted in fulfilment to the degree of Master of Arts in Political Studies to the Faculty of Humanities, University of the Witwatersrand, 2018
Keywords: Investments, Chinese; China--Foreign relations